Pengaruh Suplementasi Hidrolisat Protein Ikan Dalam Ransum Terhadap Pertumbuhan Dan Efisinsi Pakan Ayam Broiler - Rizvanda Akbar Muhamad; Adi Ratriyanto; Wara Pratitis Sabar Suprayogi; Salma Diyana Suwandana (Jurnal Ilmu Peternakan Indonesia, 2026)
Fish protein hydrolysate (FPH) is a product of enzymatic hydrolysis of fish protein yielding short-chain peptides and free amino acids with high bioavailability. This study aimed to evaluate the effect of FPH supplementation via feed, drinking water, and their combination on broiler performance including Average Daily Gain (ADG), Feed Intake (FI), Feed Conversion Ratio (FCR), and Water Intake (WI). A Completely Randomized Design (CRD) was applied with 4 treatments and 6 replicates (120 Cobb CP707 day-old chicks). Treatments consisted of P0 (control), P1 (1% powder FPH via feed), P2 (0.05% liquid FPH via drinking water), and P3 (combination of 1% powder and 0.05% liquid FPH). Birds were raised for 22 days (8–30 days of age). Analysis of variance (ANOVA) revealed significant differences (P<0.05) across all parameters. Treatment P3 produced the highest ADG (66.20 g/bird/day) and the lowest FCR (1.86), indicating superior nutrient utilization efficiency through a synergistic dual-route FPH delivery. Treatment P2 yielded the lowest ADG (51.40 g/bird/day) despite the highest water intake (105.4 mL/bird/day), suggesting that single liquid FPH supplementation was insufficient on its own. In conclusion, combined FPH supplementation via feed and drinking water (P3) is the most effective method to improve broiler production performance.